THE ART OF ILLUSTRATION IN HAMID DAMANHURI’S NOVEL THE VALUE OF SACRIFICE OR LOVE AND DUTY - Asliddin Mirzamiddinov (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the art of simile in Hamid Damunhuri’s novel The Value of Sacrifice or Love and Duty, based on sources.